Fighting Stigma, Advocating for Peace: Ainun Jamilah's Effort in Changing Society's View of Veiled Women Through the Digital Peace Movement - Alamsyah, Nayla Putri (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2025)
This study aims to explore the role of Ainun Jamilah and the Cadar Garis Lucu community in combating the negative stigma against veiled women in Indonesia, as well as to analyze the impact of the peace movement promoted through social media. The research adopts a mixed-methods approach (quantitative-qualitative) through the collection of survey data, in-depth interviews, and online observation, particularly focusing on the Cadar Garis Lucu Instagram account (@cadargarislucu). The study found a contradiction in public perceptions; where although many still view veiled women with a negative stigma, they also support the peace efforts carried out by veiled women via digital platforms. Through the Cadar Garis Lucu movement, Ainun Jamilah plays a key role in redefining the image of veiled women by promoting the values of religious moderation and peace. Through various educational content and interfaith dialogues, she facilitates, Ainun has successfully introduced a new face of veiled women as open, inclusive, and tolerant despite still facing negative stigma related to their appearance. This research contributes to the understanding of how social media can be used to advocate for peace and reduce stigma against marginalized groups. The contribution of this study lies in the application of religious moderation theory in the digital context and the use of social media to promote inclusivity and intergroup dialogue.